SOCIAL DYNAMICS OF MARRIAGE (DIVORCE) IN BANYUWANGI CITY: ECONOMIC AND CULTURAL PERSPECTIVES IN BANYUWANGI - Purnomo, Teguh; Suprihandari, Miya Dewi (Jurnal Bina Bangsa Ekonomika, 2025)
This article examines the social dynamics of marriage and divorce in Banyuwangi, East Java, Indonesia, with a focus on economic and cultural perspectives. This study aims to understand how economic factors, such as unemployment, financial instability, and job demands, contribute to the increasing divorce rate. On the other hand, this study also explores how local cultural values, including customary norms, religion, and social pressures, influence marriage and divorce decisions in Banyuwangi society. Through a qualitative approach, this study reveals the complex interactions between economic and cultural factors that shape divorce patterns, as well as their implications for the social structure and resilience of communities in Banyuwangi